2009
DOI: 10.1080/10683160802477757
|View full text |Cite
|
Sign up to set email alerts
|

Predicting guilt judgments and verdict change using a measure of pretrial bias in a videotaped mock trial with deliberating jurors

Abstract: One important limitation of previous research involving measures of bias is that they rely heavily on brief methods of conveying trial information (case summaries) and participants typically do not deliberate as juries before rendering verdicts. In the present study, 183 jury-eligible college students completed the Pretrial Juror Attitudes Questionnaire (PJAQ) and the Juror Bias Scale, watched a videotaped simulated armed robbery trial, and rendered verdicts both before and after deliberating as juries. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 46 publications
1
34
0
Order By: Relevance
“…Social science research suggests that the courts may hold an overly optimistic view of the jury's ability to correct errors, reduce bias, and follow judicial instructions (Bornstein, Whisenhunt, Nemeth, & Dunaway, 2002;Lecci & Myers, 2009;Studebaker & Penrod, 1997). For example, research has found that mock-jurors typically discuss PTP during deliberations even when admonished not to (Davis, 1986;Kline & Jess, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…Social science research suggests that the courts may hold an overly optimistic view of the jury's ability to correct errors, reduce bias, and follow judicial instructions (Bornstein, Whisenhunt, Nemeth, & Dunaway, 2002;Lecci & Myers, 2009;Studebaker & Penrod, 1997). For example, research has found that mock-jurors typically discuss PTP during deliberations even when admonished not to (Davis, 1986;Kline & Jess, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, research indicates that when more realistic trial stimuli are employed (i.e. a videotaped trail), the PJAQ can account for upwards of 21% of the variance in juror verdicts (Lecci & Myers, 2009a), and this compares favorably to other measures of pretrial bias (for a broad review of this literature see Lecci & Myers, 2009b). However, to date, the PJAQ has not been used to predict verdicts in trials involving the insanity defense.…”
Section: Assessing Pretrial Juror Attitudesmentioning
confidence: 98%
“…The PJAQ has been shown to predict verdicts across a range of case summaries with varying levels of evidence, it predicts verdicts in videotaped trials, and it provides incremental predictive validity over other measures of pretrial bias, such as the Juror Bias Scale and the Revised Legal Attitudes Questionnaire (see Lecci & Myers, 2008, 2009a, 2009b.…”
Section: Measures Pjaqmentioning
confidence: 98%
“…Because these did not overlap with any previous juror attitude measure, Lecci and Myers concluded that they reflect important new measures of juror bias. Lecci and Myers () found that the PJAQ accounted for a greater proportion of pre‐ and post‐deliberation verdicts, respectively, after statistically controlling for the JBS subscales.…”
Section: Introductionmentioning
confidence: 99%
“…First, given past research, we expected that both BRD interpretations and juror pre‐trial attitudes would independently influence verdicts. Following Lecci and Myers (), we expected that the PJAQ would have greater predictive validity compared with the JBS and RLAQ‐23 (see also Lecci & Myers, ). Second, based on the findings of Dhami (), we did not predict that the DR and MF methods would have differential predictive validity.…”
Section: Introductionmentioning
confidence: 99%